Case series – Prioritizing bladder-sparing treatments in patients with urinary tract leiomyoma: A report of three cases and updated literature review - McNall, Shannon; Park, Terry; Gopal, Nikhil; Spencer, Evan; Vemulakonda, Lakshmisree Akhila; Choudhury, Muhammad; Wong, Nathan Colin (Canadian Urological Association Journal, 2022)
Urinary tract leiomyomas are rare, benign mesenchymal tumors that are traditionally treated with complete surgical excision. We present three cases of urinary tract leiomyoma — two located in the bladder and one in the ureter. Both bladder leiomyomas were treated with transurethral resection of bladder tumor (TURBT) with no evidence of recurrent disease, while the upper tract leiomyoma was managed with surveillance by patient preference, which to our knowledge, has not been previously described. The ureteral leiomyoma has remained stable at five years followup from initial diagnosis. Given the benign nature of leiomyomas and the overall low recurrence rate reported in the literature, bladder-sparing options should be emphasized when feasible, with active surveillance potentially applicable for highly select patients.